2020
DOI: 10.1093/infdis/jiaa744
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Soluble CD14 and Tumor Necrosis Factor Receptors 1 and 2 May Be Predictive of Death in Severe Coronavirus Disease 2019

Abstract: People infected with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) display a wide range of illness, from asymptomatic infection to severe respiratory distress resulting in death. We measured serum biomarkers in uninfected individuals and in individuals with mild, moderate, or critical COVID-19 disease. Levels of monocyte activation (sCD14 and FABP4) and inflammation (TNFR1 and 2) were increased in COVID-19 individuals, regardless of disease severity. Among patients with critical disease, individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…These data highlight disruption in gut barrier integrity as a potential force that may contribute to COVID-19 severity. Our data are compatible with previous reports showed that severe COVID-19 is associated with bacterial translocation to the blood and increased levels of microbial-associated immune activation markers ( 31 , 32 ). Our results do not imply that microbial dysbiosis and translocation are the primary triggers of severe COVID-19, as the complex clinical syndrome of severe COVID-19 likely embodies multiple pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 93%
“…These data highlight disruption in gut barrier integrity as a potential force that may contribute to COVID-19 severity. Our data are compatible with previous reports showed that severe COVID-19 is associated with bacterial translocation to the blood and increased levels of microbial-associated immune activation markers ( 31 , 32 ). Our results do not imply that microbial dysbiosis and translocation are the primary triggers of severe COVID-19, as the complex clinical syndrome of severe COVID-19 likely embodies multiple pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Blood-derived prognostic biomarkers for COVID-19 infection have been heavily investigated. Inflammatory and immune factors were among the most widely studied, including serum IL-6 and TNF-α 1 , IFN-α 2 , d-dimer 3 , S100A8/A9 and HMGB1 4 , TNFR1 and TNFR2 5 , acetylated K676 TGFBIp 6 , progranulin (GRN) 7 , and sphingosine-1-phosphate 8 . Other factors include serum GDF-15 9 , calcium 10 , and fasting blood glucose 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we observed higher sCD14 in survivors and non-survivors COVID-19 patients. In line with this, Bowman and coworkers (27) found increased . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 60%
“…The copyright holder for this preprint this version posted June 27, 2021. ; https://doi.org/10.1101/2021.06.24.21259468 doi: medRxiv preprint sCD14 levels in COVID-19 patients independent of the disease severity degree. Furthermore, the authors revealed that COVID-19 critical ill patients who recovered or deceased had the highest sCD14 and lipopolysaccharide-binding protein (LBP, another marker of endotoxemia) values compared to the other groups (27). These data underlined the presence of strong activation of the monocytic lineage on hospital admission due to SARS-CoV-2 infection in conjunct with LPS translocation and inflammatory exacerbation in ICU patients (28).…”
Section: Discussionmentioning
confidence: 95%